2017
DOI: 10.1002/pen.24744
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of microparticles of partially neutralized sodium polyacrylate by inverse suspension polymerization

Abstract: The morphologies of sodium polyacrylate super absorbent polymer microparticles synthesized by inverse suspension polymerization at 658C are presented. The spherical polymer microparticles of 30-100 lm in diameter were prepared in a hydrocarbon medium with water soluble initiators in presence of a cross-linking agent and suspension stabilizer in a stirred batch reactor. A variety of microparticles morphology has been observed for different reaction conditions such as monomer/water ratio, reaction time, crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Recently, the morphologies of sodium polyacrylate SAP microparticles synthesized by inverse suspension polymerization have been reported, and it was suggested that the multihollow or porous interior structures of such microparticles can be beneficial to enhancing the waterabsorbing rate of the polymer. [2] Typically, the solution polymerization of SAPs is carried out in an aqueous medium and at relatively low temperatures in the presence of water-soluble initiator to induce the production of high molecular weight polymer chains and to avoid adversely affecting the quality of the final product. To initiate the polymerization, redox pairs are used as initiation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the morphologies of sodium polyacrylate SAP microparticles synthesized by inverse suspension polymerization have been reported, and it was suggested that the multihollow or porous interior structures of such microparticles can be beneficial to enhancing the waterabsorbing rate of the polymer. [2] Typically, the solution polymerization of SAPs is carried out in an aqueous medium and at relatively low temperatures in the presence of water-soluble initiator to induce the production of high molecular weight polymer chains and to avoid adversely affecting the quality of the final product. To initiate the polymerization, redox pairs are used as initiation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al fabricated partially neutralized sodium polyacrylate particles and investigated the effect of the reaction conditions (e.g., the type of cross-linker, monomer concentration, monomer conversion, and posttreatment) on the morphologies of the obtained particles, although they did not report details of the formation mechanism. 35,36 Here, we demonstrate morphological control of hydrophilic polymer particles with a hollow structure by applying inverse suspension polymerization via the SaPSeP method to the acid/ base hydrophilic monomers, 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS), and 1-vinylimidazole (VIm). AMPS donates a proton to VIm in water, leading to the formation of the corresponding ion complexes (AMPS anion and VIm cation), 37 which can be copolymerized by a radical initiator.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hollow hydrophilic polymer particles with an internal aqueous phase have recently received intensive attention as carriers for drugs and as (bio)­catalysts because they can encapsulate a hydrophilic material in their hydrophilic core. , Therefore, various polymerization methods have been used to prepare hollow hydrophilic polymer particles, including classical inverse suspension polymerization, interfacial polymerization, inverse Pickering suspension polymerization, , and the inverse miniemulsion periphery reversible addition–fragmentation chain transfer polymerization. , However, the literature contains only a few reports on controlling the inner morphology of hollow hydrophilic polymer particles with micron sizes via a one-step inverse suspension polymerization. Choi et al fabricated partially neutralized sodium polyacrylate particles and investigated the effect of the reaction conditions (e.g., the type of cross-linker, monomer concentration, monomer conversion, and post-treatment) on the morphologies of the obtained particles, although they did not report details of the formation mechanism. , …”
Section: Introductionmentioning
confidence: 99%
“…Water-soluble polymers are widely applied in dispersants, thickeners, flocculants, and superabsorbent polymers. Poly­(acrylic acid) (PAA) is a well-known water-soluble polymer commonly produced by aqueous solution polymerization or heterogeneous polymerization. Commercially available PAA for the applications of thickeners, flocculants, and superabsorbents is mostly in a powder form, which makes handling easier.…”
Section: Introductionmentioning
confidence: 99%